Design of a Novel 2.4GHz RF Transmitter - Tejaswi, Dhruthi; Vinay, Samudrala; Sriram, Vidyuth; M., Ananda; A.B., Kalpana (International Journal of Advanced Science Computing and Engineering, 2021)
The world of Wireless Technology has been improving consistently due to its high speed and reliability. Some of the demands that need to be fulfilled include larger network capacity, improved data rates and so on. This paper focuses on the design and simulation of the Transmitter, which is a key component in an RF Transceiver Module. It is built by cascading an Up Conversion Mixer, a Bandpass Filter and a Power Amplifier as its most fundamental units. The Cadence Virtuoso Tool was used to construct this Transmitter block in 180nm node technology. The IF signal to the Mixer is 100 MHz and the LO signal is 2.3GHz. The 2.4GHz amplified RF output is taken from the Power Amplifier. A 1dB compression point of -25.91 dBm and an IIP3 of 10.14 dBm is observed for the proposed design. Future work involves testing its integrity with an RF Receiver module that has appropriate modulation schemes in place and converting it into a physical layout-based IC.